PENGENALAN AKUNTANSI KEWAJIBAN LANCAR PADA SISWA SMA PROVIDENTIA - Dintia, Cecilia; Yanti (Jurnal Serina Abdimas, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) is an initiative by the Minister of Education and Culture aimed at encouraging students to have a comprehensive understanding in various fields of knowledge, preparing them to face the challenges of the professional world. MBKM encompasses various programs, one of which is the MBKM Teaching Program at educational institutions. This program is specifically organized for students of Providentia High School located at Jl. Kedoya Raya No.35, RT.14 /RW.7, West Jakarta. Following discussions, the team decided to provide training on current liability accounting to the students of Providentia High School. This decision was made considering the importance of understanding current liabilities for the students as they prepare for competitions. The event will involve the direct delivery of information to the participants, namely the 6 students of 12th-grade Social Sciences at Providentia High School, through face-to-face meetings scheduled from August to November 2023. After receiving positive feedback, we concluded that the chosen theme is "Introduction to Current Liability Accounting for Students of Providentia High School." Based on questionnaire results, students expressed overall positive impressions of the training. The outcomes of this activity is deeper understanding about Current Liability.